Eritrea - Health and Education Sectors : Public Expenditure Review - World Bank (Washington, DC, 2012)
Eritrea is one of the poorest countries in the world, with an average annual per capita income of US$ 200 in 2006, and ranks 157th out of 177 countries in the 2005 human development index. Rain-fed agriculture, the predominant economic activity for more than half the population, is a very risky enterprise and food security remains one of the government's main concerns. Given the security situation the government is concerned about fiscal transparency for national security reasons, but has provided access to fiscal data for a review of the education and health sectors. There have been significant improvements in access to education since independence, and improving the skills of the labor force remains critical for Eritrea's long term development. Eritrea's public resource allocation to education has increased rapidly and at 6.7 percent of Gross Domestic Product (GDP) in 2005 is slightly higher than many countries in the Africa Region. There has been a rapid expansion in tertiary education following investments in 2005 to provide an additional five colleges. The general health status of Eritrea has greatly improved since independence.